A study on consumer’s awareness, attitudes and perceptions towards genetically modified foods/ Melliscent Tony Jilat - Tony Jilat, Melliscent (2015)
The development of Genetically Modified Foods (GMFs) has been a matter considerable interest and worldwide public controversy. Genetically Modified Foods are considerable proportion of innovation in the marketplace. This is due to the world’s fastest growing recognition that addresses food safety issues and other uncertainties. This study conducted to create awareness towards consumers because they had little knowledge on genetically modified foods and they also cannot assess genetically modified foods by themselves. Furthermore, this study will provide the firm’s top management to more concern about genetically modified and also provide knowledge for the further research. The results show that the level about genetically modified food in Samarahan very low. Consumers failed to indicate or identify it appearance due to lack of labelling in packaging.